2002
DOI: 10.1002/jmr.558
|View full text |Cite
|
Sign up to set email alerts
|

Coiled coil miniprotein randomization on phage leads to charge pattern mimicry of the receptor recognition determinant of interleukin 5

Abstract: Phage display was used to identify sequences that mimic structural determinants in interleukin5 (IL5) for IL5 receptor recognition. A coiled coil stem loop (CCSL) miniprotein scaffold library was constructed with its turn region randomized and panned for binding variants against human IL5 receptor alpha chain (IL5Ralpha). Competition enzyme-linked immunosorbent assays identified CCSL-phage selectants for which binding to IL5Ralpha was competed by IL5. The most frequently selected and IL5-competed CCSL-phage co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…9 -11 Each bundle is composed of three helices (A-C) from one chain and one (D) from the other. The structure reveals two ␤-strand regions each composed of residues 88 EERRR 92 between the C-and D-helices of each four-helix bundle and an antiparallel ␤-strand from the same bundle containing another charged residue Arg 32 . Site-directed mutagenesis, as well as other studies have shown the importance of charged residues in the CD turn (in particular Glu 89 and Arg 91 ) for receptor ␣ chain binding.…”
Section: Introductionmentioning
confidence: 99%
“…9 -11 Each bundle is composed of three helices (A-C) from one chain and one (D) from the other. The structure reveals two ␤-strand regions each composed of residues 88 EERRR 92 between the C-and D-helices of each four-helix bundle and an antiparallel ␤-strand from the same bundle containing another charged residue Arg 32 . Site-directed mutagenesis, as well as other studies have shown the importance of charged residues in the CD turn (in particular Glu 89 and Arg 91 ) for receptor ␣ chain binding.…”
Section: Introductionmentioning
confidence: 99%
“…A mimic of interleukin-5 (IL5) was identified by random mutagenesis of the turn in a coiled coil miniprotein (CCSL) using the phage display technique [32]. IL5 is a homodimer comprised of two -helical bundles [33].…”
Section: Receptor Bindingmentioning
confidence: 99%